Clinical Impact of Plasma Metagenomic Next-generation Sequencing in a Large Pediatric Cohort. Issue 2 (February 2022) - Niles, Denver T.; Revell, Paula A.; Ruderfer, Daniel; Marquez, Lucila; McNeil, J. Chase; Palazzi, Debra L.
Abstract : Background: Plasma metagenomic next-generation sequencing (mNGS) has the potential to detect thousands of different organisms with a single test. There are limited data on the real-world impact of mNGS and even less guidance on the types of patients and clinical scenarios in which mNGS testing is beneficial. Methods: A retrospective review of patients who had mNGS testing as part of routine clinical care at Texas Children's Hospital from June 2018–August 2019 was performed. Medical records were reviewed for pertinent data. An expert panel of infectious disease physicians adjudicated each unique organism identified by mNGS for clinical impact. Results: There were 169 patients with at least one mNGS test. mNGS identified a definitive, probable or possible infection in 49.7% of patients. mNGS led to no clinical impact in 139 patients (82.2%), a positive impact in 21 patients (12.4%), and a negative impact in 9 patients (5.3%). mNGS identified a plausible cause for infection more often in immunocompromised patients than in immunocompetent patients (55.8% vs. 30.0%, P = 0.006). Positive clinical impact was highest in patients with multiple indications for testing (37.5%, P = 0.006) with deep-seated infections, overall, being most often associated with a positive impact. Conclusion: mNGS testing has a limited real-world clinical impact when ordered indiscriminately. Immunocompromised patients with well-defined deep-seated infections are likely to benefit most from testing. Further studies are needed to evaluate the full spectrum of clinical scenarios for which mNGS testing is impactful.